Encyclopedia of sports films - Edgington, K., 1946- (Scarecrow Press, 2010)
Whether chronicling an athlete's rise, fall, and redemption or following a team's improbable triumph on the field, sports have been a favorite theme of filmmakers almost since movies were first produced. And whether focusing on soccer (Bend It Like Beckham), boxing (Rocky and its sequels), hockey (Slap Shot), baseball (Bull Durham), football (The Longest Yard), basketball (Hoosiers), cycling (Breaking Away), or tennis (Wimbledon), such films capture the competition and thrill of sport. All major films with a primary focus on athletic endeavor are contained in Encyclopedia of Sports Films. In.